EKSISTENSI MAKHRAJ AL-JAUF - Arief Wardhani; Titin Nurhayati Makmun; Ikhwan Ikhwan (Lajnah Pentashihan Mushaf Al-Qur'an, 2018)
Abstract Al-Jauf is among five general makhraj (where the discharge letter) which is often expressed by scholars of recitation kotemporer. Meanwhile, scholars have different opinions previous recitation of existence as one makhraj letter or not. The letters that come out of this makhraj there are three, namely : alif, Wawu sukun preceded by dammah, and ya` sukun was preceded by kasrah. Three in terms of recitation referred to as mad or long vowel letters in phonetic terms. This study wants to reveal the nature of al-jauf makhraj according to the perspective of both the scholars of recitation and kotemporer previous scholars, in order to obtain a description in the pronunciation of the letters of the Koran, in particular the al-jaufiyahletter or mad letter. Keywords Al-Jauf, Tajwid, Makhraj Huruf, Huruf Mad